2018
DOI: 10.2147/copd.s147628
|View full text |Cite
|
Sign up to set email alerts
|

Missed diagnosis and overtreatment of COPD among smoking primary care population in Central Greece: old problems persist

Abstract: BackgroundThe diagnosis of COPD is not always consistent with the Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy in daily clinical practice, especially in primary care. This study aimed to estimate the overall COPD prevalence and severity, to identify differences between newly and previously diagnosed patients, and to evaluate the potential COPD overtreatment in a smoking population attending a primary care spirometry surveillance program.MethodsA study was conducted in 10 primary healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 77 publications
2
25
0
Order By: Relevance
“…In this study, ICS was prescribed in 75.7% of the patients ( Table 2). The problem of overprescription of ICS was highlighted in the literature [5,13,44,45]. For example, ICS (alone or with other medicines) was prescribed in 89, 85, 68.4, and 50% of Turkish [44], Greek [45], Greek [5], and Italian [13] COPD patients, respectively.…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, ICS was prescribed in 75.7% of the patients ( Table 2). The problem of overprescription of ICS was highlighted in the literature [5,13,44,45]. For example, ICS (alone or with other medicines) was prescribed in 89, 85, 68.4, and 50% of Turkish [44], Greek [45], Greek [5], and Italian [13] COPD patients, respectively.…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'mentioning
confidence: 99%
“…The problem of overprescription of ICS was highlighted in the literature [5,13,44,45]. For example, ICS (alone or with other medicines) was prescribed in 89, 85, 68.4, and 50% of Turkish [44], Greek [45], Greek [5], and Italian [13] COPD patients, respectively. Ten reasons BioMed Research International 7 BioMed Research International can be advanced to explain this ICS over prescription: (i) ICS is a treatment always available in hospitals; (ii) pulmonologists aim to cover all the stages/groups of COPD; (iii) lack of awareness with regard to the 2017-GOLD PTGs, even among pulmonologists [46]; (iv) repetition of the drugs previously prescribed by another physician without a cautious assessment [13]; (v) presence of wheezing [47]; (vi) high CAT score [47]; (vii) a belief that ICS are more effective [13]; (viii) higher preference for combination devices, including ICS-LABA rather than ICS and LABA in separate devices [13]; and (ix) information received from pharmaceutical companies [13].…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'mentioning
confidence: 99%
“…The relationships between the incidences and the SDI/ HDI were assessed. Notably, the prevalence of missed diagnoses of CRDs varied across all five SDI regions and countries with different HDIs, [22][23][24][25] thus affecting the estimated incidences of reported CRDs. In addition, the national epidemiologic survey on CRDs in many countries with large populations were not conducted in recent years, which may lead to an underestimation of the disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…15 studies reported overdiagnosis or misdiagnosis if the physician's diagnosis was discordant with the spirometry result, which showed either a normal or restrictive pattern [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. A physician diagnosis with normal spirometry could have been a case in which the physician did not use spirometry to establish a diagnosis of COPD (and a normal spirometry was later found in the study) [10,[14][15][16][17][21][22][23], or a case in which the physician "ignored" a normal spirometry result [12,20,24]. Most of these studies cited underutilisation of spirometry as the primary cause of overdiagnosis and misdiagnosis in this context.…”
Section: Physician Copd Diagnosis But With Normal Spirometrymentioning
confidence: 99%
“…Eight studies considered these cases to be misdiagnosed [14,15,[18][19][20][21][22]24]. In two studies the terms "overdiagnosis" and misdiagnosis were used interchangeably to describe this concept [16,23].…”
Section: Physician Copd Diagnosis But With Normal Spirometrymentioning
confidence: 99%